Improving the Students’ Motivation and Learning Outcomes With Picture and Picture Method By Using Vivocom Fold Book Media - Amaliah, Amaliah (Jetlal, 2017)
The purpose of this study is to describe the improvement of students’ motivation in learning, as well as the students’learning outcomes by using Vivocom Fold Book media with communicative method, picture and picture. The writer uses experimental method, with the design of one group experiment by comparing before and after mark in narrative learning; conducted in class 9-11 at SMPN 2 Sidoarjo. The result is (1) The use of Vivocom Fold Book media can increase students’ motivation to learn English from less motivated, become very motivated in learning, that is from index 2.16 to 4.53 in very motivated category, (2) The use of Vivocom Fold Book can improve students’ learning outcomes, from 71% classical completeness to 91% of total students 35. Vivocom Fold Book Media is very complete. It can motivate andfacilitate students to understand English narrative texts. Media Vivocom Fold Book is also designed specifically to overcome the limitations of vocabulary and understanding the structure of the text, promoting the moral value contained in Indonesian folklores in international language.